COVID-19 and Cancer: A guide with suggested COVID-19 rule- out criteria to support clinical decision-making (2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a highly contagious zoonotic pathogen that has exacted heavy public health, social and economic tolls. In February 2020, the World Health Organization acronymed the disease caused by SARS-CoV-2 as COVID-19, for coronavirus disease 2019. The number of confirmed COVID-19 infections, which has been detected in at least 103 countries, has reached 1,970,225 worldwide as of April 14, 2020 with 124,544 deaths, according to the U.S. Centers for Disease Control and Prevention (CDC).1 Many cases of COVID-19 resolve quickly. However, the disease, which, like other respiratory pathogens that cause common cold symptoms is believed to be transmitted through respiratory droplets. Infection with COVID-19 can also lead to significant morbidity and death; this is particularly the case for cancer patients. Moreover, because the signs and symptoms of COVID19 are easily misattributed to the sequelae of cancer itself, such as pulmonary embolism, or its treatment, such as nausea and diarrhea, diagnosis may be delayed or missed. Potential COVID19 rule out criteria, based on the Wells‘ criteria for pulmonary embolism, another protean disease entity, are provided as a decision-making aid. This review summarizes the current understanding of the transmission, clinical presentation, diagnosis and differential diagnosis, pathogenesis, rationale to treat the cancer or not, treatment and prevention of COVID-19 with an emphasis on implications in cancer.